The effect of real exchange rate volatility on income distribution in South Africa - Goodness C. Aye; Laurence Harris (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This study investigates the effect of real exchange rate volatility on the distribution of income between labour and capital in South Africa. Both symmetric and asymmetric effects are considered. Using quarterly data for 1985:1-2018:3 and local linear projection, we find that the immediate response of labour's income share to a one standard deviation shock in exchange rate volatility is negative. Moreover, high exchange rate volatility impacts negatively on labour's income share, while low exchange rate volatility impacts positively on labour income. As the magnitude of the effect of high exchange rate volatility is greater than that of low exchange rate volatility, the study documents evidence of an asymmetric effect. A shock increase in some control variables (real gross domestic product, investment, and openness) is followed immediately by a decline in labour income, while an increase follows a positive shock in the relative price of investment. The policy implications of these findings are discussed.
Keywords: E25; F31; F41; J38; 330; functional distribution of income; inequality; real effective exchange rate volatility; South Africa; uncertainty